2006
DOI: 10.1002/jae.866
|View full text |Cite
|
Sign up to set email alerts
|

Sectoral labour supply, choice restrictions and functional form

Abstract: In this paper we discuss a general framework for analyzing labor supply behavior in the presence of complicated budget-and quantity constraints of which some are unobserved. The point of departure is that an individual's labor supply decision can be considered as a choice from a set of discrete alternatives (jobs). These jobs are characterized by attributes such as hours of work, sector specific wages and other sector specific aspects of the jobs. We focus in particular on theoretical justification of function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 91 publications
(149 citation statements)
references
References 36 publications
3
146
0
Order By: Relevance
“…From Table A1, we observe that the sample selection variable has an insignificant effect. The effects of schooling and experience are consistent with findings in previous analyses using Norwegian data (see, for example, Dagsvik and Strøm, 2006). In agreement with our a priori belief we find, ceteris paribus, that females living in densely populated areas have higher expected real wage rates than females living in sparsely populated areas.…”
Section:  supporting
confidence: 92%
“…From Table A1, we observe that the sample selection variable has an insignificant effect. The effects of schooling and experience are consistent with findings in previous analyses using Norwegian data (see, for example, Dagsvik and Strøm, 2006). In agreement with our a priori belief we find, ceteris paribus, that females living in densely populated areas have higher expected real wage rates than females living in sparsely populated areas.…”
Section:  supporting
confidence: 92%
“…We follow an alternative approach, based on Dagsvik and Jia (2006) and Dagsvik and Strøm (2006): labor supply behavior is viewed as an outcome of agents choosing from a set of job "packages", each of which is characterized by an offered wage rate, offered hours of work and nonpecuniary (qualitative) attributes describing the nature of the job-specific tasks to be performed. Thus, the hours of work of a given job are assumed fixed.…”
Section: Modeling Labor Supply: An Alternative Methodologymentioning
confidence: 99%
“…Dagsvik and Strøm (2004) showed that the model is identified under the restriction that g(.) is a distribution function over the possible positive hours of work.…”
Section: The Terms G(h) H > 0 Are Called Opportunity Densitiesmentioning
confidence: 99%
See 2 more Smart Citations